Effect of Eurycoma longifolia Stem Extract on Uric Acid Excretion in Hyperuricemia Mice - Bao, Ruixia; Liu, Mengyang; Wang, Dan; Wen, Shaoshi; Yu, Haiyang; Zhong, Yi; Li, Zheng; Zhang, Yi; Wang, Tao (Frontiers in Pharmacology, 2019)
Background:Eurycoma longifolia is a tropical medicinal plant belonging to Simaroubaceae distributed in South East Asia. The stems are traditionally used for the treatment of sexual insufficiency, fever, hypertension, and malaria. Furthermore, it has antidiabetic and anticancer activities. Recently, it has been reported to reduce uric acid, but the mechanism is unclear. Hypothesis/Purpose: The aim of this study is to explore the effect and mechanism of E. longifolia stem 70% ethanol extract (EL) and its active compounds on uric acid excretion. Study Design and Methods: Potassium oxonate (PO) induced hyperuricemia rats model and adenine-PO induced hyperuricemia mice model were used to evaluate the effects of EL. Ultraperformance liquid chromatography was used to determine the levels of plasma or serum uric acid and creatinine. Hematoxylin-eosin staining was applied to observe kidney pathological changes, and western blot was applied to detect protein expression levels of uric acid transporters. Effects of constituents on urate uptake were tested in hURAT1-expressing HEK293T cells. Results: EL significantly reduced serum and plasma uric acid levels at dosages of 100, 200, and 400 mg/kg in hyperuricemia rats and mice, increased the clearance rate of uric acid and creatinine, and improved the renal pathological injury. The protein expression levels of urate reabsorption transporter 1 (URAT1) and glucose transporter 9 were down-regulated, while sodium-dependent phosphate transporter 1 and ATP-binding cassette transporter G2 were up-regulated in the kidney after EL treatment. The quassinoids isolated from EL showed inhibitory effects on urate uptake in hURAT1-expressing HEK293T cells, and the effect of eurycomanol was further confirmed in vivo. Conclusion: Our findings revealed that EL significantly reduced blood uric acid levels, prevented pathological changes of kidney in PO induced hyperuricemia animal model, and improved renal urate transports. We partly clarified the mechanism was related to suppressing effect of URAT1 by quassinoid in EL. This study is the first to demonstrate that EL plays a role in hyperuricemia by promoting renal uric acid excretion.